Pengaruh Metode Pembelajaran Kooperatif Jigsaw Terhadap Kemampuan Komunikasi Matematis Ditinjau Berdasarkan Kepribadian Siswa - islah ziauddin sardar yeubun (Wahana Matematika dan Sains: Jurnal Matematika, Sains, dan Pembelajarannya, 2020)
This study uses a quasi-experimental method with the final design control test of mathematical communication skills in terms of student personality through personality tests. The sample of this study was students of class XI-IPS in MAN 6 Kampung Dukuh and MAN 6 Cibubur East Jakarta in the odd semester 2018/2019 Academic Year as many as 88 people. The instrument used in this study is a description question and personality questionnaire. The results showed that 1) The ability of mathematical communication students who got the cooperative jigsaw method was higher than the students who received conventional learning, 2) There were interactions between learning methods and personalities on mathematical communication skills, 3) Mathematical communication skills of students with extroverted personalities given jigsaw cooperative method treatment is higher than those given conventional learning treatment, 4) Mathematical communication skills of students with introverted personalities treated with cooperative jigsaw methods are lower than those given conventional learning treatments. Thus, jigsaw cooperative learning is better applied to students with an extracurricular personality.